Motivational interviewing to increase physical activity in women with gestational diabetes. (2nd October 2021) - Smith, Ralph; Ridout, Ashley; Livingstone, Angus; Wango, Nicola; Kenworthy, Yvonne; Barlett, Katy; Coburn, Hazel; Reid, Hamish; Jones, Natasha; Mackillop, Lucy
Abstract : Regular physical activity improves glycaemic control in pregnant women with gestational diabetes. Motivational interviewing is an effective technique for increasing activity levels. This report evaluates a clinical pathway developed to integrate physical activity motivational interviewing into routine gestational diabetes care. Women attending a single-centre NHS clinic were invited to engage in a physical activity-focused motivational interview. The aerobic physical activity levels of 62 women were evaluated at baseline and at a 2-week telephone follow up, coded into three categories by minutes of moderate intensity physical activity per week: red (<30 minutes), amber (30–149 minutes) and green (≥150 minutes). At baseline, 30.6% of participants were coded red, 41.9% amber and 27.4% green. At follow up, 4.8% women coded red, 38.7% amber and 56.5% green, demonstrating a significant association for increased activity levels after motivational interviewing ( P <0.001). This clinical pathway provides encouraging results that physical activity increased significantly in the short term.